Fugetaxis of Cell-in-Catalytic-Coat Nanobiohybrids in Glucose Gradients - Rheem, Hyeong Bin; Choi, Hyunwoo; Yang, Seoin; Han, Sol; Rhee, Su Yeon; Jeong, Hyeongseop; Lee, Kyung-Bok; Lee, Yeji; Kim, In-San; Lee, Hojae; Choi, Insung S. S. (Wiley - V C H Verlag GmbbH & Co., 2023)
Manipulation and control of cell chemotaxis remain an underexplored territory despite vast potential in various fields, such as cytotherapeutics, sensors, and even cell robots. Herein is achieved the chemical control over chemotactic movement and direction of Jurkat T cells, as a representative model, by the construction of cell-in-catalytic-coat structures in single-cell nanoencapsulation. Armed with the catalytic power of glucose oxidase (GOx) in the artificial coat, the nanobiohybrid cytostructures, denoted as Jurkat([Lipo_GOx]), exhibit controllable, redirected chemotactic movement in response to d-glucose gradients, in the opposite direction to the positive-chemotaxis direction of naive, uncoated Jurkat cells in the same gradients. The chemically endowed, reaction-based fugetaxis of Jurkat([Lipo_GOx]) operates orthogonally and complementarily to the endogenous, binding/recognition-based chemotaxis that remains intact after the formation of a GOx coat. For instance, the chemotactic velocity of Jurkat([Lipo_GOx]) can be adjusted by varying the combination of d-glucose and natural chemokines (CXCL12 and CCL19) in the gradient. This work offers an innovative chemical tool for bioaugmenting living cells at the single-cell level through the use of catalytic cell-in-coat structures.